Mental fatigue impairs visuomotor response time in badminton players and controls - Van Cutsem, J.; De Pauw, K.; Vandervaeren, C.; Marcora, S.; Meeusen, R.; Roelands, B. (Psychology of Sport and Exercise, 2019)
Highlights